Physiological demands and muscle activity of "track-work" riding in apprentice jockeys - Legg, K. A.; Cochrane, D. J.; Gee, E. K.; Macdermid, P. W.; Rogers, C. W. (International Journal of Sports Physiology and Performance, 2022)
Purpose: To enhance performance in race riding, knowledge of current training workload is required. The objectives of this study were to quantify the physiological demands and profile the muscle activity of jockeys riding track-work.